(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2015)
Dating the Tempietto sul Clitunno is still a subject of controversy, although so many studies have be-en made during the last two centuries and above all in the last few years. Some authors in 18th and 19th cen-turies thought the Tempietto was a “pagan” sacellum from the beginning and only successively transformed to serve christian functions; other authors, on the contrary, are of the opinion that the foundations of the building were laid in the early christian age; some other authors date it to the early medieval age and think it represents an important monument belonging to the longobard architecture of the Duchy of Spoleto.